2022
DOI: 10.9734/indj/2022/v17i130190
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral and Ameliorative Effect of Complan Milk and Bambara Nut on Rats Fed With Bitter Cassava – A Nutritional Approach

Abstract: Cassava products have been introduced to the market in different regions of the world as part of diet, despite containing more than one toxic substance. Roots and leaves of cassava of all varieties contain cyanogenic glucoside, mainly as linamarin, but also as lotaustralin, in different concentrations in their cellular vacuoles. Twenty (20) albino Wistar rats were used for this research and were randomly selected into 4 groups of five 5 rats each. The result obtained from the study showed that there was a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In a study also done by Enefa et al [6] there was significant reduction in weight in animal fed with cassava due to the presence of cyanide in cassava which was in keeping with our study. Shama et al [16] and David et al [10] posited also in their studies that there was a reduction in weight of the Wistar rats fed with unprocessed cassava rich cyanogenic glycosides also indicating the effect of cassava on weight.…”
Section: Discussion Of Findingsmentioning
confidence: 91%
See 1 more Smart Citation
“…In a study also done by Enefa et al [6] there was significant reduction in weight in animal fed with cassava due to the presence of cyanide in cassava which was in keeping with our study. Shama et al [16] and David et al [10] posited also in their studies that there was a reduction in weight of the Wistar rats fed with unprocessed cassava rich cyanogenic glycosides also indicating the effect of cassava on weight.…”
Section: Discussion Of Findingsmentioning
confidence: 91%
“…This group were the first to demonstrate cognitive impairment with konzo [3,4], after earlier electroencephalographic studies suggested cortical involvement [1,5]. Not much study has been carried out on konzo disease using animal models, but in recent times, a neuroscience researcher in Nigeria, David Lekpa Kingdom, has been carrying out in-vivo study into the neurological effect of bitter cassava induced konzo disease using rat models to better understand the mechanism in which konzo affects the neural system [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The cortex was scraped using a cutter shortly after harvesting to reveal the whitish interior layer. The cassava roots were then chopped into tiny pieces, similar to pommes frites, and sun-dried for three days as described by Enefa et al, [30] and David et al, [31].…”
Section: Bitter Cassava Root Processingmentioning
confidence: 99%
“…The method of Konzo induction is as described by David et al, [31] and David et al, [32] with slight modification. Bitter cassava chow was made from pommes frites cassava that was grinded into a powdered form using a grinding machine and fed to the animals used for the experiment for the period of 5 weeks.…”
Section: Induction Of Konzomentioning
confidence: 99%
See 1 more Smart Citation